Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Microvertebrates from the Cliff End Bone Bed (Wealden, Lower Cretaceous), East Sussex, UK - Johnny Clavo Yamahuchi; Elizabeth Cook; Christopher J. Duffin; Peter A. Austen; Steven C. Sweetman; Pamela G. Gill; Claudia Hildebrandt; Tim Tomkinson; Michael J. Benton (Proceedings of the Geologists' Association, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Longitudinal patterns of urinary biomarkers of placental and renal function in pregnancy and associations with early pregnancy exposure to phthalates and replacements - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Reproductive Toxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Insights from U.S. beekeeper triage surveys following unusually high honey bee colony losses 2024–2025 - Anthony Nearman; Christopher L. Crawford; M. Marta Guarna; Priyadarshini Chakrabarti; Katie Lee; Steven Cook; Elizabeth Hill; Arathi Seshadri; Garett Slater; Zachary S. Lamas; Yan Ping Chen; Danielle Downey; et al. (Science of The Total Environment, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Exposure to phthalates and replacements during pregnancy in association with gestational blood pressure and hypertensive disorders of pregnancy - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Emma M. Rosen; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Environmental Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Assessing the Effects of Physical Barriers and Hypoxia on Red Drum Movement Patterns to Develop More Effective Management Strategies - Steven M. Baker; Eric A. Reyier; Bonnie J. Ahr; Geoffrey S. Cook (Fishes, 2023)
Human modification of coastal ecosystems often creates barriers to fish movement. Passive acoustic telemetry was used to quantify movement patterns and habitat use of red drums (Sciaenops ocellatus) within and around a complex of coastal impoundments, and explored how the presence of artificial structures (i.e., bollards and culverts) and a hypoxia-related mortality event impacted fish movement. Results indicated bollards impede the movement of individuals with head widths greater than the mean distance between bollards (~16.0 cm). Red drum home range area and daily distance traveled were related to water dissolved oxygen concentrations; as oxygen levels decreased, fish habitat use area decreased initially. However, continued exposure to hypoxic conditions increased fish cumulative daily distance traveled. When exposed to anoxic waters, fish daily distance traveled and rate of movement were greatly reduced. These findings suggest prolonged exposure to low dissolved oxygen in combination with artificial structures can reduce movement of red drum, increase risk of mortality, and decrease habitat connectivity. Constructing and maintaining (sediment and biofouling removal) larger culvert openings and/or using wider bollard spacing would improve water circulation in impoundments, increase habitat connectivity, and facilitate movement of large sportfish inhabiting Florida’s coastal waters.

Foresight science in conservation: Tools, barriers, and mainstreaming opportunities - Gabrielle Ednie; Tyreen Kapoor; Olga Koppel; Morgan L. Piczak; Jessica L. Reid; Alyssa D. Murdoch; Carly N. Cook; William J. Sutherland; Steven J. Cooke (Ambio, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Resistance to amitraz in the parasitic honey bee mite Varroa destructor is associated with mutations in the β-adrenergic-like octopamine receptor - Carmen Sara Hernández-Rodríguez; Sara Moreno-Martí; Gabrielle Almecija; Krisztina Christmon; Josephine D. Johnson; Marie Ventelon; Dennis vanEngelsdorp; Steven C. Cook; Joel González-Cabrera (Journal of Pest Science, 2022)
Varroa destructor is considered a major reason for high loss rate of Western honey bee ( Apis mellifera ) colonies. To prevent colony losses caused by V. destructor, it is necessary to actively manage the mite population. Beekeepers, particularly commercial beekeepers, have few alternative treatments other than synthetic acaricides to control the parasite, resulting in intensive treatment regimens that led to the evolution of resistance in mite populations. To investigate the mechanism of the resistance to amitraz detected in V. destructor mites from French and U.S. apiaries, we identified and characterized octopamine and tyramine receptors (the known targets of amitraz) in this species. The comparison of sequences obtained from mites collected from different apiaries with different treatment regimens, showed that the amino acid substitutions N87S or Y215H in the OctβR were associated with treatment failures reported in French or U.S. apiaries, respectively. Based on our findings, we have developed and tested two high throughput diagnostic assays based on TaqMan technology able to accurately detect mites carrying the mutations in this receptor. This valuable information may be of help for beekeepers when selecting the most suitable acaricide to manage V. destructor .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Novel Application of Photogrammetry to Quantify Fascicle Orientations of Female Cadaveric Pelvic Floor Muscles - Megan R. Routzong; Mark S. Cook; William Barone; Steven D. Abramowitch; Marianna Alperin (Annals of Biomedical Engineering, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Persistence of Chlorpropham (CIPC) in the Concrete Flooring of Potato Stores - Leisa Douglas; Gillian MacKinnon; Gordon Cook; Harry Duncan; Adrian Briddon; Steven Seamark (Potato Research, 2018)

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Using an in vitro system for maintaining Varroa destructor mites on Apis mellifera pupae as hosts: studies of mite longevity and feeding behavior - Noble I. Egekwu; Francisco Posada; Daniel E. Sonenshine; Steven Cook (Experimental and Applied Acarology, 2018)

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)

Abuse-related effects of subtype-selective GABAA receptor positive allosteric modulators in an assay of intracranial self-stimulation in rats - Kathryn L. Schwienteck; Guanguan Li; Michael M. Poe; James M. Cook; Matthew L. Banks; S. Stevens Negus (Psychopharmacology, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Mortality risk from comorbidities independent of triple-negative breast cancer status: NCI-SEER-based cohort analysis - Helen Swede; Amna Sarwar; Anil Magge; Dejana Braithwaite; Linda S. Cook; David I. Gregorio; Beth A. Jones; Jessica R. Hoag; Lou Gonsalves; Andrew L. Salner; Kristen Zarfos; Biree Andemariam; et al. (Cancer Causes & Control, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

C-Terminal trans-activation sub-region of VP16 is uniquely required for forskolin-induced herpes simplex virus type 1 reactivation from quiescently infected-PC12 cells but not for replication in neuronally differentiated-PC12 cells - Robert J. Danaher; Ross K. Cook; Chunmei Wang; Steven J. Triezenberg; Robert J. Jacob; Craig S. Miller (Journal of NeuroVirology, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

An Evaluation of Techniques to Control Problem Bird Species on Landfill Sites - Aonghais Cook; Steven Rushton; John Allan; Andrew Baxter (Environmental Management, 2008)

Mitochondrial DNA reveals multiple Northern Hemisphere introductions of Caprella mutica (Crustacea, Amphipoda) - GAIL V. ASHTON; MARK I. STEVENS; MARK C. HART; DAVID H. GREEN; MICHAEL T. BURROWS; ELIZABETH J. COOK; KATE J. WILLIS (Molecular Ecology, 2008)
Caprella mutica (Crustacea, Amphipoda) has been widely introduced to non‐native regions in the last 40 years. Its native habitat is sub‐boreal northeast Asia, but in the Northern Hemisphere, it is now found on both coasts of North America, and North Atlantic coastlines of Europe. Direct sequencing of mitochondrial DNA (cytochrome c oxidase subunit I gene) was used to compare genetic variation in native and non‐native populations of C. mutica . These data were used to investigate the invasion history of C. mutica and to test potential source populations in Japan. High diversity (31 haplotypes from 49 individuals), but no phylogeographical structure, was identified in four populations in the putative native range. In contrast, non‐native populations showed reduced genetic diversity (7 haplotypes from 249 individuals) and informative phylogeographical structure. Grouping of C. mutica populations into native, east Pacific, and Atlantic groups explained the most among‐region variation (59%). This indicates independent introduction pathways for C. mutica to the Pacific and Atlantic coasts of North America. Two dominant haplotypes were identified in eastern and western Atlantic coastal populations, indicating several dispersal routes within the Atlantic. The analysis indicated that several introductions from multiple sources were likely to be responsible for the observed global distribution of C. mutica , but the pathways were least well defined among the Atlantic populations. The four sampled populations of C. mutica in Japan could not be identified as the direct source of the non‐native populations examined in this study. The high diversity within the Japan populations indicates that the native range needs to be assessed at a far greater scale, both within and among populations, to accurately assess the source of the global spread of C. mutica .

Incubation reduces microbial growth on eggshells and the opportunity for trans‐shell infection - Mark I. Cook; Steven R. Beissinger; Gary A. Toranzos; Wayne J. Arendt (Ecology Letters, 2005)
Avian eggshells harbour microbes shortly after laying, and under appropriate ambient conditions they can multiply rapidly, penetrate through shell pores, infect egg contents and cause embryo mortality. We experimentally examined how incubation affects bacterial processes on the eggshells of pearl‐eyed thrashers Margarops fuscatus nesting in tropical montane and lowland forests in Puerto Rico. Bacteria and fungi grew rapidly on shells of newly laid, unincubated eggs exposed to ambient conditions, but declined to low levels on shells of eggs incubated by thrashers. Divergence in bacterial growth between incubated and exposed eggs was more marked at the montane forest than at the lowland site. Pathogenic microorganisms became increasingly dominant on shells of exposed eggs, but these groups were relatively rare on incubated eggs, where more benign, less invasive groups prevailed. Some incubation during laying may be necessary to decrease the probability of trans‐shell infection by reducing the growth of harmful bacteria and fungi on eggshells, although it may increase hatching asynchrony and the likelihood of brood reduction.

Liquid-feeding performances of ants (Formicidae): ecological and evolutionary implications - Diane W. Davidson; Steven C. Cook; Roy R. Snelling (Oecologia, 2005)

Liquid-feeding performances of ants (Formicidae): ecological and evolutionary implications - Diane W. Davidson; Steven C. Cook; Roy R. Snelling (Oecologia, 2004)

Diversity, Distribution, and Ancient Taxonomic Relationships Within the TIR and Non-TIR NBS-LRR Resistance Gene Subfamilies - Steven B. Cannon; Hongyan Zhu; Andrew M. Baumgarten; Russell Spangler; Georgiana May *, Douglas R. Cook (Journal of Molecular Evolution, 2002)

Environmental Impacts of Acid Leachate Derived from Coal-Storage Piles upon Groundwater - Angie M. Cook; Steven J. Fritz (Water, Air, & Soil Pollution, 2002)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)